Postablation Stimulated Thyroglobulin Level is an Important Predictor of Biochemical Complete Remission after Reoperative Cervical Neck Dissection in Persistent/Recurrent Papillary Thyroid Carcinoma - Lang, Brian Hung-Hin (Springer-Verlag, 2012)
BACKGROUND: The efficacy of reoperative cervical neck dissection (RND) in achieving biochemical complete remission (BCR) (or postreoperation stimulated thyroglobulin [sTg] of <0.5 ng/mL) remains unclear in persistent/recurrent papillary thyroid carcinoma (PTC). We hypothesized that lower postablation sTg levels would indicate a higher rate of BCR after RND. Our study examined the association between postablation sTg and BCR after one or more RNDs. METHODS: Of 199 patients who underwent RND, 81 patients were eligible. The postablation sTg levels (≤2 and >2 ng/mL) were correlated with the postreoperation sTg levels after RNDs. Patients’ clinicopathological characteristics, operative findings, and subsequent RNDs were compared between those with BCR after RNDs and those without. RESULTS: Those with postablation sTg levels of ≤2 ng/mL had significantly higher BCR rate after the first RND (77.8 vs. 5.6 %, p < 0.001), overall BCR after one or more RNDs (77.8 vs. 9.3 %, p < 0.001), and better 5-year recurrence-free survival after the first RND (80.0 vs. 60.1 %, p = 0.049) than those with postablation sTg levels of >2 ng/mL. Overall BCR gradually decreased after each subsequent RND. Postablation sTg significantly correlated with postreoperation sTg (ρ = 0.509, p < 0.001). After adjusting for the number of metastatic lymph nodes excised at first RND and presence of extranodal extension, postablation sTg of ≤ 0.2 ng/mL was the only independent factor for BCR after one or more RNDs (odds ratio 37.0, 95 % confidence interval 5.68–250.0, p = 0.001). CONCLUSIONS: Only a third of patients who underwent one or more RNDs for persistent/recurrent PTC had BCR afterward. Postablation sTg level was an independent factor for BCR. Completeness of the initial operation is important for the subsequent success of RND.